Phytochemical Profiling Of Berberis Aristata Roots: Identification Of Bioactive Compounds And Their Pharmacological Potential - Prem Prasad Dhungana, (Journal of Contemporary Review, 2025)
In Nepal Berberis aristata locally known as Chutro. It is a important highly medicinal plant used for the treatment of disease in traditional Ayurvedic and Himalayan medicine. The plant contains some phytochemical constituents like alkaloids, flavonoids, tannins, phenolics, terpenoids, and saponins. These phytochemicals show strong antimicrobial, antioxidant, anti-inflammatory, hepatoprotective, and anti-diabetic effects. This study find  the major classes of phytochemicals present in B. aristata, their chemical nature, plant part distribution, and their pharmacological importance. Findings from previous studies show that alkaloids like berberine, palmatine, and jatrorrhizine play key roles in antimicrobial and cytoprotective effects, while flavonoids and phenolic compounds contribute significantly to antioxidant activity.There was siginficant chemical test done to know to identified chemical constituent present in B. aristata.